Penerapan Daun Sirih Hijau dan Madu terhadap Penyembuhan Luka Perineum Ibu Post Partum - Tika Kusuma Dewi; Fida’ Husain (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Background: Perineal wounds are wounds due to tearing of the birth canal either due to rupture or due to episiotomy at the time of delivery of the fetus. One of the impacts of normal labor is the risk of perineal infection. The prevalence in Indonesia of post partum infection reaches 7.3% and ranks third in causes of death after bleeding. For this reason, it is necessary to make efforts in taking care of the wound to keep it clean and dry, and avoid infection. Objective: Application of betel leaf and honey decoction to accelerate the healing process of perineal wounds. Methods: This type of research uses descriptive research methods and observes 2 respondents with post partum conditions and is given the implementation of wound care carried out in Boyolali with the application time of June 18, 2024-June 24, 2024. Results: The REEDA score after being given the intervention experienced an improved status with a comparison of the results of the application of the 7th action on the first respondent, the initial REEDA score of 2 decreased to 0 while the application of the 7th action on the second respondent, the initial REEDA score of 1 decreased to 0. Conclusion: There is an effect on the application of wound care using betel leaf decoction water and honey which shows that green betel leaves and honey are effective in healing perineal wounds.